Association between bilateral sagittal split osteotomy setback and autorotation of the mandible - Syeda Fathimuz Zahara; Nandish Shetty; Pooja Harish; Akhter Husain (Wolters Kluwer Medknow Publications, 2023)
Introduction: The study aimed to evaluate the autorotation for Class III malocclusions after the bilateral sagittal split osteotomy (BSSO) setback procedure. Methodology: This retrospective study includes lateral cephalograms of eight males and three females total of 11 patients who had undergone BSSO, without any other additional surgeries. The Frankfurt-Horizontal (F-H) plane was used as a reference and manual superimposition was done. Considering stable mandibular landmarks, reference line perpendicular (RLp) and reference line (RL) were drawn as x and y coordinates, respectively. Pre- and postsurgical statistics were used to compare using paired t-test where P < 0.05 was set for statistical significance. Results: Superimposed tracings showed no significant difference in pre- and postsurgical treatments. There was no statistically significant amount of autorotation after the BSSO setback procedure (P = 0.714). Conclusion: Hence, BSSO setback surgery will not cause any significant amount of autorotation of the mandible. If autorotation is required it must be incorporated into treatment planning.